The Role of Religious Communities in the Adoption, Implementation, and Monitoring of the United Nations Convention on the Rights of the Child, With a Special Regard to the Role of the Holy See - Benyusz , Márta (Religion and Children’s Rights, 2025)
Abstract:The United Nations Convention on the Rights of the Child (hereinafter, UNCRC or Convention), being the most widely ratified human rights treaty in the world,1 bears the influence of different stakeholders who played an important role in the drafting process, its adoption, and later in its implementation and monitoring. The most important stakeholders are the State Parties to the Convention, who are the primary duty bearers of the obligations stemming from it. There are other stakeholders, such as the United Nations Children’s Fund (hereinafter, UNICEF), non-governmental organisations (hereinafter, NGOs), national human rights institutions (hereinafter, NHRIs)2 and religious communities. The Holy See is party to the UNCRC, and therefore is a primary duty bearer just as other State Parties. Thus, from the perspective of international law and from a narrower aspect, from the perspective of the UNCRC among religious communities, the role and the impact of the Holy See and by implication the Catholic Church is the most tangible from a legal point of view. The current chapter elaborates the role of religious communities in the drafting, adoption, implementation, and monitoring of the UNCRC. The first part of the paper will give a general overview of the impact of religious communities. The second and core part of the paper will focus on the role of the Holy See, the representative of the Catholic Church and belief – unlike representatives of other religions – has an own status in international law and the ability to enter international conventions. Keywords: UNCRC, children’s rights, religious communities, Holy See, Vatican City, Catholic Church, safeguarding, rights-based approach, reporting cycle, Committee on the Rights of the Child, Pontifical Commission for the Protection of Minors and Vulnerable Adults, world religions